Deus Est Caritas: The Voice of Gabriele Biondo on Personal Justification and Church Reform - Guida, Vito. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
The book examines the life and the writings of Gabriele Biondo, a secular priest who lived in the little town of Modigliana between the second half of the fifteenth century and the first decades of the sixteenth century. Through a careful examination of his writings and the sources he used, this book allows the reader to obtain a more precise understanding of Biondo, his background, his life, his movements, the difficulties that he encountered (mainly with the ecclesiastical authorities and the other members of the clergy, but also with civic leaders), and the main events of his life. Additionally, Biondo was the leader of a minor following formed by nuns, secular women, and laymen. Therefore, this book illustrates Biondo's pastoral activity, the ideas and principles that supported his actions, and the objectives he was pursuing. Given these various objectives, this book is of interest to those scholars and academics interested in the religious tensions that swept through Europe in the years immediately preceding the Protestant Reformation and who, consequently, seek to investigate Biondo's personal and complex answer to these tensions.
1. Introduction: Religious Crisis and the Debate between Divine Love and Justice -- 2. The Life and the Works of Gabriele Biondo -- 3. Philology, Auctoritates, and Source -- 4. Falling out of Love with God: A Spiral Descent into Self-Annihilation -- 5. The Grace of God: The Path of Divine Justification and Personal Redemption through Obedience and Spogliamento -- 6. Extra ecclesiam nulla salus: Salvation within the Ecclesiastical Sphere -- 7. Conclusions -- Bibliography.
Keywords: Religion -- Philosophy; Science -- History; Philosophy; Philosophy of Religion; History of Science; Intercultural Philosophy and Religious Traditions